Highly Absorbent Ultrafast Self‐Gelling Starch Microparticles for Robust Wet‐Tissue Adhesion and Instant Hemostasis - Soohwan An; Jihoon Jeon; Seung Yeop Han; Mi Jeong Lee; Tae‐Gyeong Oh; Eun Je Jeon; Dong Jin Joo; Seung‐Woo Cho (Advanced Science)
Abstract Rapid and effective hemostasis of mass bleeding from irregularly shaped wounds remains a critical clinical challenge. Herein, a highly absorbent and self‐gelling microparticle (MP) is reported based on modified starch as a hemostatic material with robust wet tissue adhesiveness. The aldehyde‐ and catechol‐modified starch (ACS) is synthesized via partial oxidation of starch for the reduction of dense intermolecular interactions within starch, thereby significantly enhancing its interaction with water molecules. Moreover, the conjugated catechol group strengthens the affinity to various biomolecules. The ACS microparticle (ACS‐MP) prepared by calcium intercalation into the polysaccharide chains and subsequent freeze‐milling rapidly converts to a stable hydrogel within seconds upon hydration, exhibiting superior water absorption capacity and tissue adhesion. The ACS‐MP demonstrates excellent in vivo biocompatibility in local and systemic administration. The application of ACS‐MP to bleeding wounds enables rapid blood absorption and accumulation of blood components and coagulation factors. The ACS‐MP can fill irregularly shaped wounds, forming a tissue‐adhesive hydrogel in situ, thereby creating a physical barrier for non‐compressible hemostasis. The superior hemostatic performance of ACS‐MP against massive hemorrhage from liver injuries in mice and pigs is confirmed. The ACS‐MP will be a promising hemostat for effectively controlling mass bleeding in various tissues in clinical settings.